2014
DOI: 10.5194/nhessd-2-427-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atmospheric processes triggering the Central European floods in June 2013

Abstract: Abstract. In June 2013 Central Europe was hit by a century flood affecting the Danube and Elbe catchments after a 4 day period of heavy precipitation and causing severe human and economic loss. In this study model analysis and observational data are investigated to reveal the key atmospheric processes that caused the heavy precipitation event. The period preceeding the flood was characterised by a weather regime associated with cool and unusual wet conditions resulting from repeated Rossby wave breaking (RWB).… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 39 publications
7
77
0
Order By: Relevance
“…Gochis and Coauthors () found quasi‐stationary weather systems because of a blocking pattern helped to set up large‐scale flow patterns, which triggered several mesoscale circulation features in the great Colorado flood. Grams et al () found that a quasi‐stationary COL initiated multiple consecutive low pressure systems travelling along an abnormal track, resulting in a few days of heavy precipitation, which triggered the 2013 central Europe flood. It is common to all three events that the quasi‐stationary synoptic system maintained the large‐scale circulation during the event, which provided the required heat and moisture fluxes, although the individual weather system that directly produced extreme precipitation could be a single quasi‐stationary low pressure system, such as in the Alberta flood, or a few consecutive travelling cyclones, such as in the great Colorado and central European floods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gochis and Coauthors () found quasi‐stationary weather systems because of a blocking pattern helped to set up large‐scale flow patterns, which triggered several mesoscale circulation features in the great Colorado flood. Grams et al () found that a quasi‐stationary COL initiated multiple consecutive low pressure systems travelling along an abnormal track, resulting in a few days of heavy precipitation, which triggered the 2013 central Europe flood. It is common to all three events that the quasi‐stationary synoptic system maintained the large‐scale circulation during the event, which provided the required heat and moisture fluxes, although the individual weather system that directly produced extreme precipitation could be a single quasi‐stationary low pressure system, such as in the Alberta flood, or a few consecutive travelling cyclones, such as in the great Colorado and central European floods.…”
Section: Discussionmentioning
confidence: 99%
“…Gochis and Coauthors () identified that the long‐range transport of moisture from the Gulf of Mexico was one of the primary sources for the great Colorado flood, and Grams et al () argued that continental evaporation provided significant moisture support for the central European flood in June 2013. Among these three extreme flooding events in 2013, evapotranspiration over land played an important role in the Alberta and central European floods in June.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extreme events like the central European floods in 2002 (Ulbrich et al, 2003a) and 2013 (Grams et al, 2014), the heat waves in 2003 (Schär et al, 2004) and 2010 (Barriopedro et al, 2011) and winter storms "Lothar" in 1999 (Wernli et al, 2002) and "Klaus" in 2009 (Liberato et al, 2011) caused severe damages and various fatalities in Europe. A characterisation of the processes leading to such meteorological extreme events and a proper representation of these processes in climate models is central for assessing potential future changes in the occurrence of weather extremes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A number of rivers, mostly within the Danube, Rhine, and Elbe river basins, exceeded warning thresholds and several cities suffered from damage and service disruption caused by the floods. Further details on the flood and on the underlying atmospheric processes are described by Blöschl et al (2013) and by Grams et al (2014). Cdf of the probability of the ERI exceeding the 2, 5, and 20-year return period (event peak), with contour lines at significant probability levels.…”
Section: Case Study -The Central European Floods Of June 2013mentioning
confidence: 99%